2012
DOI: 10.1186/1756-3305-5-143
|View full text |Cite
|
Sign up to set email alerts
|

Identity and diversity of blood meal hosts of biting midges (Diptera: Ceratopogonidae: Culicoides Latreille) in Denmark

Abstract: BackgroundHost preference studies in haematophagous insects e.g. Culicoides biting midges are pivotal to assess transmission routes of vector-borne diseases and critical for the development of veterinary contingency plans to identify which species should be included due to their risk potential. Species of Culicoides have been found in almost all parts of the world and known to live in a variety of habitats. Several parasites and viruses are transmitted by Culicoides biting midges including Bluetongue virus and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
87
1
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(98 citation statements)
references
References 40 publications
(65 reference statements)
6
87
1
1
Order By: Relevance
“…Haemoproteus prevalence was higher for species that nest between 1 and 5 m above ground level than for species that nest below 1 m or above 5 m. Because canopy heights in our early-successional habitats were low, this pattern is consistent with the observation that Haemoproteus vectors are more abundant in forest canopies (Garvin and Greiner 2003;Cerný et al 2011;Lassen et al 2012). Other studies have found similar positive associations between nesting height and parasite prevalence (Fecchio et al 2011;González et al 2014;Lutz et al 2015), while still others have failed to find an association (Ricklefs et al 2005;Fecchio et al 2013).…”
Section: Nesting Heightsupporting
confidence: 88%
“…Haemoproteus prevalence was higher for species that nest between 1 and 5 m above ground level than for species that nest below 1 m or above 5 m. Because canopy heights in our early-successional habitats were low, this pattern is consistent with the observation that Haemoproteus vectors are more abundant in forest canopies (Garvin and Greiner 2003;Cerný et al 2011;Lassen et al 2012). Other studies have found similar positive associations between nesting height and parasite prevalence (Fecchio et al 2011;González et al 2014;Lutz et al 2015), while still others have failed to find an association (Ricklefs et al 2005;Fecchio et al 2013).…”
Section: Nesting Heightsupporting
confidence: 88%
“…Thus, possible vector-parasite associations between C. alazanicus and haemoproteids with local transmission are supposed. Moreover, recent studies have revealed that C. alazanicus, together with C. circumscriptus and C. festivipennis, demonstrate ornithophilic feeding preferences (Lassen et al 2012;Pettersson et al 2012;Bobeva et al 2014). In addition, haemosporidian parasites have been previously detected in the latter two species (Ferraguti et al 2013;Synek et al 2013;Bobeva et al 2013).…”
Section: Discussionmentioning
confidence: 97%
“…Greenwood and Booker (2016) similarly found that small body size was a characteristic trait of invertebrate assemblages from streams with more pasture upstream, though this was associated with strong rather than poorly dispersing taxa. In our study, only one trait indicative of greater dispersal, long female flight distances, was characteristic of the agricultural streams, associated with blood-feeding Diptera (Ceratopogonidae and Simuliidae) that have females which disperse farther in search of meals (Lassen et al 2012;McCreadie and Adler 2012). The influence that this might have on connectivity between freshwater and terrestrial habitats is demonstrated by Carlson et al's (2016) finding that the proportion of blood feeding Ceratopogonidae was associated with greater dispersal distance by adult Diptera overall.…”
Section: Discussionmentioning
confidence: 99%